Influence Of Technohumanism And Dateism On Education Of Information Society - Сухова, Н. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Introduction. The information revolution, started in the middle of the twentieth century, today embraces all spheres from production sphere to mankind’s social activity. Free access to information resources, changing forms of man’s communication, encouraging reformatting of the educational space and changing the principles of governing society. The scale of human intelligence has changed causing man’s ability to develop new forms of relationships, to create services, to change the outer world without worrying about the ecology of our planet and his own soul. Thus, the working-human world, in which there are flint organisms alongside proteinaceous organisms - robots, implies many ambiguous risks for humanity. In the scientific literature discussions are raising regarding the influence on the human consciousness of technohumanism and datism, which are the foundations of transhumanism. Ways of origin of these concepts have their reasons in society, today it is necessary to analyze them in detail in order to find ways to solve urgent issues of humanity as soon as possible. The aim and tasks. Technohumanism and Dateism of the XXIst century threaten human society, eradicating humanity in favor of new technologies. Therefore, the aim and the tasks of the article are to consider the reasons for the emergence and influence of technohumanism and datism on the formation of new worldview educational guidelines in a globalized world. Research methods. To achieve this goal, it is advisable to use a synergistic approach that will enable us to understand the ambiguity and complexity of the transformation processes of modern society as a self-organizing system, since education is the most conservative branch of human existence, which significantly influences its formation. A comparative approach will help fruitfully compare the research findings of scientists from different fields of scientific knowledge, their forecasts and worldviews regarding the need to pay attention to the ecology of the human soul. Discussion. The problem of the influence of such forms of transhumanism as technohumanism and dateism on man’s education of the XXI century is fruitfully discussed in the scientific community. The main reason for the emergence of these phenomena is the need for society to address health problems and facilitate work in difficult and harmful conditions for human beings, facilitate the processing of information accumulated by the human society, the management of society and so on. Analyzing the negative tendencies of the implementation of technohumanism and dateism in life, the researchers unanimously emphasize the need to preserve humanity in a person of information age, which is possible only if the use of inventions of bio, nano and information technologies is restricted. Many researchers say that today humanity is faced with new problems of information and ecological nature: virtualization of interpersonal communication, information security of society and personality, management of mass consciousness, information wars, Internet addiction of various levels, computer gaming, computer gaming, computer gaming, human cyborgization in the context of artificial intelligence creation and the like. There is a problem of clarification of questions concerning access to information, its quality. Most social media-filled data cannot be called information at all. The dissemination of questionable facts and information is a trap for the immature consciousness of users being manipulated and infected ideologically. Therefore, the so-called "pure" information will remain unclaimed without certain codes and keys. The main issue today is to distinguish true information from unnecessary one. This is a task for the educational field, since the main priority is to develop a persons’ thinking so that they can adequately perceive, evaluate and analyze the information they receive, and subsequently be able to use it productively in their lives. Conclusion. Humanity is very slowly moving to a new level of complexity, it often does not even outline its future, confusedly trying to plan life in a changing information world. Yet, the search for new forms of humanism that fits the spirit of the times and the cultural model of society is proceeding. There is nowhere to escape from the digital world where one finds it difficult to hide his data in. Our freedom in the future will be the result of the collective actions, which are not possible without communication, without public resonance. Describing the negative impact of technohumanism and datism on the educational field of man, scientists in the technical and natural sciences often do not take into account the hidden spiritual basis of all things. Therefore, it is important to take philosophy away from society. By reducing and even losing courses in the disciplines of the philosophical cycle in higher education, humanity is losing its orientation from the whole. Effective managers, who are the most sought after people in a fragmented world, know how to activate what is needed to achieve the goal of fragmentary change. They can see where they are going, but they cannot understand why, do not see the whole and therefore their activities are doomed to fail in the future. The whole arises at a different level of imagination. From this level follows a fundamentally new vision of the prospects of human existence. Therefore, it is not surprising that the education of the XXIst c. became only a part of social policy, losing its fateful value to humanity. In approaching environmental catastrophe, when environmental laws are violated, elementary rules of morality are ignored, etc., we will have to make one-for-all decisions using the best prospects of the information age. And today, instead of predicting the future, it is important to engage in its formation.